Causes Of Gout, Symptoms And Methods Of Prevention, As Well As Treatment Prophylaxis - Kayumova, Zebo (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article provides information on the causes of gout, its manifestations and symptoms, preventive measures and treatment measures, and a brief literature review.